2007
DOI: 10.1080/03014460601080983
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status, growth, physical activity and fitness: The Madeira Growth Study

Abstract: Background: Within a country social conditions change over time and these conditions vary from country to country. The associations between these conditions, somatic growth, physical activity and fitness reflect these changes. Aim: The study documented variation in somatic growth, physical activity and fitness associated with socio-economic status (SES). Subjects and methods: The study involved 507 subjects (256 boys and 251 girls) from the Madeira Growth Study, a mixed longitudinal study of five cohorts (8, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
67
5
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 31 publications
12
67
5
2
Order By: Relevance
“…The present findings should, however, be interpreted with some caution, because we cannot rule out sample bias as an explanation (Tables II and III). Although we did not observe a clear, direct association between SES and physical fitness in children from Bogotá, as has been shown to some extent, elsewhere, 5,7,27 the present data do suggest that area-level SES may influence fitness to a greater extent than family income. This may be because this is a better indicator of local-area amenities that provide children with the opportunity to develop or maintain fitness via access to safe play areas or sporting infrastructure.…”
Section: Avena (Feeding and Assessment Of Nutritional Status Ofcontrasting
confidence: 72%
See 4 more Smart Citations
“…The present findings should, however, be interpreted with some caution, because we cannot rule out sample bias as an explanation (Tables II and III). Although we did not observe a clear, direct association between SES and physical fitness in children from Bogotá, as has been shown to some extent, elsewhere, 5,7,27 the present data do suggest that area-level SES may influence fitness to a greater extent than family income. This may be because this is a better indicator of local-area amenities that provide children with the opportunity to develop or maintain fitness via access to safe play areas or sporting infrastructure.…”
Section: Avena (Feeding and Assessment Of Nutritional Status Ofcontrasting
confidence: 72%
“…24,25 Freitas et al 7 reported better Jump performance in girls in the high vs low SES groups but no differences in boys. Using a multifactorial index of SES, Jiminez Pavon et al 5 found that Jump distance increased across children in the low, moderate, and high SES groups, after adjusting for age, height, and adiposity but not sociogeographic factors or potential clustering.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations